STRATEGI PEMASARAN UDANG VANNAMEI (Litopenaeus vannamei) DI KECAMATAN GALIS KABUPATEN PAMEKASAN - Sa'edi, Sa'edi; Pudjiastuti, Agnes Quartina; Mutiara, Farah (Fakultas Pertanian, 2018)
Marketing strategy is a form of desicion making about marketing costs, marketing mix, marketing allocation in relation to the expected environmental condition, the aims of this reseach to find out the marketing strategy, marketing system and analysis of vannamei shrimp farming in Galis District. This research was conducted in Galis Subdistrict , Pamekasan Regency. This study was analyzed by looking at the strengths, weaknesses, opportunities and treats (SWOT). Based on the IFE and EFE matrix so as to produce an IE matrix. The results of the study show that marketing of shrimp in Galis Subdistrict uses a vertical marketing, the production of shrimp farmers is directly sold to traders (CV.WINDU JAYA) from Bangil Pasuruan. Shrimp farming business in Galis Subdistrict is a business category that is developing and has excellent potential to support farmer’s income receved is Rp. 346.022.661,25. While the shrimp infrastructure margin is Rp. 68.436.976,25. Strategi pemasaran adalah suatu bentuk pengambilan keputusan tentang biaya pemasaran, bauran pemasaran, alokasi pemasaran dalam hubungan dengan keadaan lingkungan yang diharapkan. Penelitian ini bertujuan untuk menganalisis strategi pemasaran, sistem pemasaran dan usahatani udang vannamei di Kecamatan Galis Kabupaten Pamekasan. Data dianalisis dengan melihat kekuatan, kelemahan, peluang dan ancaman (SWOT). Berdasarkan matriks IFE dan EFE sehingga menghasilkan matriks IE. Hasil penelitian menunjukkan bahwa pemasaran udang di Kecamatan Galis Kabupaten Pamekasan menggunakan sistem pemasaran vertikal. Hasil produksi udang dari petani langsung dijual ke pedagang (CV.WINDU JAYA) dari Bangil Pasuruan. Usaha tambak udang di Kecamatan Galis Kabupaten Pamekasan termasuk kategori usaha yang sedang berkembang dan mempunyai potensi yang sangat baik untuk menunjang pendapatan dan kesejahteraan petani. Keuntungan yang di peroleh petani sebesar Rp. 346.022.661,25 sedangkan margin pemasaran udang sebesar Rp. 68.436.976,25.